​Exploring the experience of people at-risk of Non-alcoholic Fatty Liver Disease in making and maintaining lifestyle changes - Mehta, Rhian Mehta (2024)
Objectives. Non-alcoholic fatty liver disease (NAFLD) is a growing health concern where lifestyle change is the cornerstone of treatment. With advancements in technology, individuals with risk factors for NAFLD can undergo liver screening within the community and are advised to make lifestyle changes; however, little is known about patient experiences and what influences long term lifestyle change in this patient population. The study therefore aimed to qualitatively explore patient experiences of lifestyle change and whether being identified as at risk of NAFLD influenced this. Design. Qualitative semi-structured interviews were conducted. Method. Thirteen participants identified as at risk of NAFLD who received transient elastography (TE) and maintained weight loss or dietary change as indicated by self-report measures participated in interviews. Data was analysed using reflexive thematic analysis. Results. Four themes were developed: ‘Preservation of health’; ‘It’s me that’s got to do it’; ‘Flexible determination’; ‘Make it gradual, make it manageable’. Findings indicated that participants viewed comorbid health conditions or aspects of aging as more prominent, with the risk of NAFLD often being low due to the lack of symptoms and ongoing support. There was a shared dissatisfaction with current NAFLD provision and advice around weight loss with advice often being experienced as blaming. Participants shared how a gradual and flexible approach supported them to maintain changes overtime. Conclusion. The findings emphasise the importance of (1) clinicians providing more information and tailored lifestyle advice for NAFLD (2) emphasis being placed on tangible markers of health, particularly in the absence of NAFLD specific symptoms.